GREEN ENERGY PROGRAM TO SUPPORT SUSTAINABLE ECOTOURISM: IMPLEMENTATION OF SOLAR POWER PLANT IN MALASIGI TRADITIONAL VILLAGE SORONG REGENCY SOUTHWEST PAPUA INDONESIA - Saribanon, Nonon; Putra, Njo Fransiscus Xaverius Anditya Ciptadi; Amarullah, Amarullah; Ramadhan, Muhammad Ishlah; Prihandini, Viola Ayu (Journal of Social Political Sciences, 2025)
Green energy initiatives play a vital role in advancing sustainable ecotourism, particularly in remote regions characterized by rich biodiversity yet limited infrastructure. This study investigates the implementation of an 8,700-watt Solar Power Plant (SPP) in the Malasigi Traditional Village, Southwest Papua, and its contribution to supporting ecotourism operations and fulfilling the basic needs of the local community. Employing a qualitative descriptive methodology, the research assesses the SPP’s impact on energy efficiency, carbon emission reductions, service quality enhancement in ecotourism, and local economic empowerment. The findings reveal that the integration of the SPP significantly supports ecotourism development by supplying electricity for essential services such as clean water access, lighting, and operational facilities for visitors and residents. Notably, the SPP implementation has led to a reduction in diesel fuel consumption by approximately 3,600 liters annually and a corresponding decrease in carbon emissions of 9.02 tons CO₂eq per year. Furthermore, the community experienced a 53% reduction in energy-related expenditures. These outcomes underscore the strategic value of renewable energy technologies as a foundational component for promoting environmentally sustainable, economically viable, and socially inclusive ecotourism in remote areas.